Translation and validation of the music-related quality of life questionnaire for adults with cochlear implant in Turkish language - ÇİPRUT, AYŞE AYÇA (SPRINGER, 2022)
Purpose It is important to assess the impact of music on cochlear implant (CI) users' quality of life. The aim of this study was to adapt and validate the music-related quality of life questionnaire into the Turkish language for adult CI users. Methods 161 CI users and 162 normal-hearing adults were included in the study. The final Turkish version of the questionnaire was prepared and evaluated for validity and reliability. The internal consistency of the questionnaire and test-retest reliability were evaluated by Cronbach's alpha and ICC index. Factor analysis and 'know-group' method was used to determine the construct validity. Results Sampling adequacy for execution of factor analysis was confirmed by the results of Kaiser-Meyer-Olkin (= 0.91) and Bartlett test (p < 0.05). 2 factors for each scale were identified from exploratory factor analysis. Confirmatory factor analysis confirmed the questionnaire met the criteria standards for adequacy of fit. The reliability coefficient was determined at least 0.80. Correlation between items indicated excellent (> .80) internal consistency. Conclusion The Turkish version of the questionnaire has good validity and reliability and can be used to investigate the relationship between music and quality of life and as a diagnostic tool in identifying individuals who need music support and to guide and evaluate music rehabilitation.
Keywords: Cochlear implant; Quality of life; Music; Validity; Reliability; Adaptation